Active Photoswitching of Sharp Fano Resonances in THz Metadevices - Manjappa, Manukumara (2017)
Fano resonances offer exciting features in enhancing the non-linearity and sensing capabilities in metamaterial systems. An active photoswitching of Fano resonances in a terahertz metadevice at low optical pump powers is demonstrated, which signifies the extreme sensitivity of the high-quality-factor resonant electric field to the external light illumination.